Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/pim.12709
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and goblet cell gene expression in equine cyathostomin infection and larvicidal anthelmintic therapy

Abstract: Aims:The role of the immune response to cyathostomin infections in horses remains unknown. Intestinal goblet cell hyperplasia has previously been noted as a component in cyathostomin infection; however, the function is unclear. The goal of this study was to evaluate the local and systemic gene expression to cyathostomin infections following larvicidal treatment and explore their relation to goblet cells. Methods and Results: Thirty-six ponies with naturally acquired cyathostomin infections were randomly alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Previous studies have evaluated the inflammatory reaction to ivermectin and compared it to oxibendazole, moxidectin and a few other products 2,11,19 . These studies noted no differences between the treatment groups; however, intestinal erythema, oedema and ulceration following worm burdens were noted, 2,19,20 which is consistent with our previous findings 14,21 …”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies have evaluated the inflammatory reaction to ivermectin and compared it to oxibendazole, moxidectin and a few other products 2,11,19 . These studies noted no differences between the treatment groups; however, intestinal erythema, oedema and ulceration following worm burdens were noted, 2,19,20 which is consistent with our previous findings 14,21 …”
Section: Introductionsupporting
confidence: 86%
“…2,11,19 These studies noted no differences between the treatment groups; however, intestinal erythema, oedema and ulceration following worm burdens were noted, 2,19,20 which is consistent with our previous findings. 14,21 Only one study, thus far, has evaluated cytokine gene expression in large intestinal tissues of horses with and without large intestinal disease, including three cases of larval cyathostominosis. 22 They found that tumour necrosis factor (TNF)-α was expressed in horses with inflammatory bowel disease; however, there were no significant differences between the groups with and without large intestinal disease.…”
Section: Introductionmentioning
confidence: 99%
“…have previously been associated with inflammation in the gut and detected in humans and mice prior to the onset of colitis [24]. Recently Steurer et al [25] reported an interaction between larvicidal anthelmintic treatment, cyathostomin expulsion from the mucosa and MUC2 gene expression in goblet cells following moxidectin treatment. These data lead us to speculate that an increase in the relative abundance of Deferribacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…According to the available knowledge, goblet cells are an integral part of the organ epithelial barrier and produce mucin products and play an important role in the immune response to mucosal antigens (e.g., parasites) [ 31 ]. The observed congestion of blood in the vessels may result from the formation of blood clots, which is a consequence of the release of inflammatory mediators from damaged epithelial and/or endothelial cells (activation of the antifibrinolytic coagulation cascade) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%